Enhanced controllable triplet proximity effect in superconducting spin–orbit coupled spin valves with modified superconductor/ferromagnet interfaces - Alex Bregazzi; JA Ouassou; Arthur Coveney; NA Stelmashenko; A Child; AT N'Diaye; JWA Robinson; Fasil Dejene; J Linder; N Banerjee (2024)
In a superconductor/ferromagnet hybrid, a magnetically controlled singlet-to-triplet Cooper pair conversion can modulate the superconducting critical temperature. In these triplet superconducting spin valves, such control usually requires inhomogeneous magnetism. However, in the presence of spin–orbit coupling from an interfacial heavy metal layer, the singlet/triplet conversion rate and, thus, critical temperature can be controlled via the magnetization direction of a single homogeneous ferromagnet. Here, we report significantly enhanced controllable pair conversion to a triplet state in a Nb/Pt/Co/Pt superconducting spin valve in which Pt/Co/Pt is homogenously magnetized and proximity-coupled to a superconducting layer of Nb. The Co/Pt interface furthest away from Nb is modified by a sub-nanometer-thick layer of Cu or Au. We argue that the enhancement is most likely associated from an improvement of the Co/Pt interface due to the insertion of Cu and Au layers. Additionally, the higher normalized orbital moments in Au measured using x-ray magnetic circular dichroism shows that increasing spin–orbit coupling enhances the triplet proximity effect—an observation supported by our theoretical calculations. Our results provide a pathway to enhancing triplet pair creation by interface engineering for device development in superspintronics.